2009
DOI: 10.1371/journal.pone.0007081
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Validation of a Real-Time PCR Assay for Detection and Quantitation of Human Adenovirus 14 from Clinical Samples

Abstract: In 2007, the Centers for Disease Control and Prevention (CDC) reported that Human adenovirus type 14 (HAdV-14) infected 106 military personnel and was responsible for the death of one U.S. soldier at Lackland Air Force Base in Texas. Identification of the responsible adenovirus, which had not previously been seen in North America and for which rapid diagnostic tools were unavailable, required retrospective analysis at reference laboratories. Initial quarantine measures were also reliant on relatively slow trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The IScript One-Step RT-PCR Kit for probes was used (Bio-Rad: Hercules, CA) with Ad Hex forward (5'-GGGTTGAAACTACTGAAGAACG-3'), reverse (5'CATCTGTATCAGTCCACG ATT-3') primers, and probes that target hypervariable regions 1–6 of the hexon gene previously described. 18 The following cycling conditions were followed: initial denaturing cycle at 95.0°C for 15 minutes followed by 45 cycles of denaturation at 95.0°C for 1 s, annealing at 60.0°C for 15 s, and extension at 72.0°C for 10 s. Three different independent assays were run in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…The IScript One-Step RT-PCR Kit for probes was used (Bio-Rad: Hercules, CA) with Ad Hex forward (5'-GGGTTGAAACTACTGAAGAACG-3'), reverse (5'CATCTGTATCAGTCCACG ATT-3') primers, and probes that target hypervariable regions 1–6 of the hexon gene previously described. 18 The following cycling conditions were followed: initial denaturing cycle at 95.0°C for 15 minutes followed by 45 cycles of denaturation at 95.0°C for 1 s, annealing at 60.0°C for 15 s, and extension at 72.0°C for 10 s. Three different independent assays were run in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Ad14-specific NAATs have been described, but are generally used only for epidemiologic studies. 139 RVs are best identified by RT-PCR targeting the 5 0 UTR performed on respiratory secretions from infected individuals. Although relatively highly conserved in comparison with RV coding regions, sequence variation in the 5 0 UTR between different RV types creates difficulties in designing primer pairs that can satisfactorily detect all RV types and species.…”
Section: Diagnosismentioning
confidence: 99%
“…The rapidity of real-time PCR is extremely helpful in the clinical setting, especially in outbreaks and epidemics. Recently, Metzgar et al [34] described the increased utility of real-time PCR, especially in detection of pathogenic serotype 14. Their study showed that PCR had a higher sensitivity and specificity for serotype 14, with no known cross-reactivity with other respiratory viral pathogens [34].…”
Section: Diagnosismentioning
confidence: 99%